2007
DOI: 10.1016/j.heares.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic–electric interactions in the guinea pig auditory nerve: Simultaneous and forward masking of the electrically evoked compound action potential

Abstract: The study investigated the time course of the effects of acoustic and electric stimulation on the electrically evoked compound action potential (ECAP). Adult guinea pigs were used in acute experimental sessions. Bursts of acoustic noise and high-rate (5000 pulses/s) electric pulse trains were used as maskers. Biphasic electric pulses were used as probes. ECAPs were recorded from the auditory nerve trunk.Simultaneous masking of the ECAP with acoustic noise featured an onset effect and a decrease in the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 42 publications
11
36
0
Order By: Relevance
“…However, those data were obtained under different conditions, i.e., using single, electric, masking pulses and chemically deafened ears. The results obtained from hearing ears stimulated by relatively long-duration (400 ms) acoustic maskers, as in the Nourski et al (2007) study, could differ substantially. Clearly, ANF measures are needed to identify the specific ANF response properties that underlie changes in the gross potential.…”
Section: Goals and Rationalesmentioning
confidence: 72%
See 3 more Smart Citations
“…However, those data were obtained under different conditions, i.e., using single, electric, masking pulses and chemically deafened ears. The results obtained from hearing ears stimulated by relatively long-duration (400 ms) acoustic maskers, as in the Nourski et al (2007) study, could differ substantially. Clearly, ANF measures are needed to identify the specific ANF response properties that underlie changes in the gross potential.…”
Section: Goals and Rationalesmentioning
confidence: 72%
“…Post-masking reductions in spike rate, within-fiber jitter and acrossfiber variance in latency were found, with the changes in temporal response properties limited to ANFs with high spontaneous rates. Thus, our results suggest how non-monotonic ECAP recovery occurs for ears with spontaneous activity, but cannot account for that pattern of recovery when there is no spontaneous activity, including the results from the presumably deafened ears used in the Nourski et al (2007) study. Finally, during simultaneous (electric+acoustic) stimulation, the degree of electrically driven spike activity had a strong influence on spike rate, but did not affect spike jitter, which apparently was determined by the acoustic noise stimulus or spontaneous activity.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…A second is that the electrical stimulation is driving depolarization and hair cell neurotransmitter release and that this contributes to the afferent fiber compound action potentials observed in the vECAP. Studies recording ECAPs from stimulation of the auditory nerve have suggested that hair cells themselves can contribute directly to ECAP amplitudes (Miller et al 2006;Nourski et al 2007;Van Den Honert and Stypulkowski 1984). It is also possible that the afferent fibers were at a lower galvanic threshold due to tonic unstimulated neurotransmitter release prior to gentamicin lesion of the hair cells and were therefore more responsive to direct galvanic stimulation.…”
Section: Preexisting Peripheral Lossmentioning
confidence: 99%